2015
DOI: 10.12659/msm.893855
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Embolism in Cardiac Myxoma: A Retrospective Analysis

Abstract: BackgroundMyxomas are the most common primary heart tumors and are closely associated with embolic events. Cardiac myxomas typically arise from the interatrial septum at the border of the fossa ovalis in the left atrium. Any other location is considered atypical. Embolism, one of the complications of myxoma, is associated with high morbidity and mortality. The aim of this study was to investigate the risk factors for embolism in patients with cardiac myxoma.Material/MethodsIn this retrospective study, a cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…6 Complications can involve mechanical complications such as valvular obstruction, and embolisation has been reported in 30%-50% of patients. 7 By far the most common embolic complication is stroke, which accounts for over 80% of embolic phenomenon. 8 In contrast, metastatic involvement of the myocardium through haematogenous spread, direct invasion or tumour growth through the vena cava into the right atrium is relative common with an incidence of 8% in one large postmortem study of patients who died from cancer, with a particularly high frequency of myocardial involvement observed in squamous cell carcinoma of the lung (62%), urinary tract tumours (60%) and melanoma (45%).…”
Section: Unusual Association Of Diseases/symptoms Discussionmentioning
confidence: 99%
“…6 Complications can involve mechanical complications such as valvular obstruction, and embolisation has been reported in 30%-50% of patients. 7 By far the most common embolic complication is stroke, which accounts for over 80% of embolic phenomenon. 8 In contrast, metastatic involvement of the myocardium through haematogenous spread, direct invasion or tumour growth through the vena cava into the right atrium is relative common with an incidence of 8% in one large postmortem study of patients who died from cancer, with a particularly high frequency of myocardial involvement observed in squamous cell carcinoma of the lung (62%), urinary tract tumours (60%) and melanoma (45%).…”
Section: Unusual Association Of Diseases/symptoms Discussionmentioning
confidence: 99%
“…Recently, it was reported that tumor location, macroscopic appearance, mean platelet volume, and high platelet count are strong risk factors for embolic events in patients with cardiac myxomas. 5 Although most published series report that immediate surgery is necessary to avoid embolism, the authors planned surgical resection for the following week. What is the meaning of the following week?…”
Section: To the Editormentioning
confidence: 99%
“…A genetic to 2.5% of patients, in the left ventricle in 0.7% to 3.6% of patients, and in a heart valve (aortic, mitral) in fewer than 1% of patients. 1,4,9,11,13,19,20,24 Most studies reported that CM was identified in the left atrium in about 72% to 92% patients. 2,5,15 The fossa ovalis in the interatrial septum was the most common site to which CM, with or without a broad base, was attached.…”
mentioning
confidence: 99%
“…13,21 Epidemiology Cardiac myxoma is a rare benign cardiac tumor, and its incidence is observed in approximately 0.5-1 cases per 1 million people per year. 1,4,11,24 The condition may develop in all ages, more frequently in women than in men. The demographic characteristics of patients included in this review are listed in TABLE 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation